Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1007/bf00210984
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit articular chondrocytes in alginate gel: characterisation of immobilized preparations and potential applications

Abstract: Primary cultivated rabbit articular chondrocytes were immobilized in calcium alginate beads. Both free and entrapped cells were allowed to grow under normal conditions. After long-term immobilization, the cells still exhibited metabolic activities, patterns of division, synthesis and secretion of extracellular matrix macromolecules such as type II collagen and proteoglycans. After 38 days, immobilized rabbit articular chondrocytes predominantly expressed type II but not type I collagen. Thus, they maintained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Since three-dimensional culture could maintain the phenotype for a long culture period, it is more practical to investigate the influence of serum chondrocytes cultured in three-dimensional scaffolds. It was proved that alginate scaffold biomaterial has a great potential in cartilage tissue scaffolds for cartilage tissue engineering [5, 8, 9, 23], thus we adopted alginate hydrogel as a three-dimensional scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since three-dimensional culture could maintain the phenotype for a long culture period, it is more practical to investigate the influence of serum chondrocytes cultured in three-dimensional scaffolds. It was proved that alginate scaffold biomaterial has a great potential in cartilage tissue scaffolds for cartilage tissue engineering [5, 8, 9, 23], thus we adopted alginate hydrogel as a three-dimensional scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate hydrogel is a frequently used scaffold for cartilage engineering. After long-term immobilization culture, rabbit articular chondrocytes in alginate gel still exhibited metabolic activities, patterns of division, as well as synthesis and secretion of extracellular matrix macromolecules such as type II collagen and proteoglycans [8]. Allogenic implants of chondrocytes in alginate gels was tested for the in vivo reconstruction of artificially full-thickness-damaged articular rabbit cartilage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical shifts were referenced by using 4.68 ppm for the HDO signal (secondary standard for 3-(trimethylsilyl)-lpropaiiesulfonic acid (DSS) at 0.00 ppm). The 'H NMR experiments were repeated several times (solution, n = 10; agarose, n = 5; low density alginate, n = 3; high density alginate, n = 5).…”
Section: Samplesmentioning
confidence: 99%
“…A matrix that appears to share many of the physicochemical properties of normal cartilage matrix, is formed around the entrapped cells (Buschmann et al, 1992). Several studies have now established that the entrapment of isolated Chondrocytes in agarose gel helps to promote the synthesis of collagen type II and keratan sulphate-containing aggrecan, which are markers of the chondrocytic phenotype (Benya and Shaffer, 1982;Aydelotte et al, 1991; have also been entrapped in alginate (Kupchik et al, 1983;Guo et al, 1989;Häuselmann et al, 1992;Tamponnet et al, 1992;Chan et al 1993). It has been demonstrated that rabbit articular chondrocytes cultured for 38 days (Guyot et al, 1990) and bovine adult articular chondrocytes cultured for 8 months (Häuselmann et al, 1994) in Ca-alginate beads have retained their phenotype and are synthesising collagens and proteoglycans that are typical of those found in the cartilage matrix from which the cells are isolated.…”
Section: Animal Cellsmentioning
confidence: 95%